Respuesta :

37. (3/4)(x -3) < (1/3)(x -4)
Most folks like to eliminate fractions first. To do that, you can multiply by 12.
  9(x -3) < 4(x -4)
Now, eliminate parentheses.
  9x -27 < 4x -16
Subtract 4x to put the variable on one side only. Add 27 to put the constant on the other side only.
  5x < 11
Divide by the coefficient of x to get x by itself.
  x < 11/5


39. You can actually work these without eliminating fractions. Just do the arithmetic in the usual way.
Eliminate parentheses.
  (2/5)(3 -2n) ≥ (3/8)(2 -3n)
  6/5 -(4/5)n ≥ 3/4 -(9/8)n
Add (9/8)n -6/5
  n(9/8 -4/5) ≥ 3/4 -6/5
  (13/40)n ≥ -9/20
Multiply by the inverse of the coefficient of n
  n ≥ (-9/20)*(40/13)
  n ≥ -18/13
ACCESS MORE